Plant salicylic acid signaling is inhibited by a cooperative strategy of two powdery mildew effectors - Yuhan Liu; Xiao Li; Qiguang He; Minghao Zuo; Yinjie Guo; Lijuan Liu; Jinyao Yin; Lijuan He; Xiaoli Li; Jiaxin Shan; Wenbo Liu; Chunhua Lin; et al. (mBio)
ABSTRACT Powdery mildew is a global threat to crops and economically valuable plants. Salicylic acid (SA) signaling plays a significant role in plant resistance to biotrophic parasites; however, the mechanisms behind how powdery mildew fungi circumvent SA-mediated resistance remain unclear. Many phytopathogenic microbes deliver effectors into the host to sustain infection. In this study, we showed that the rubber tree powdery mildew fungus Erysiphe quercicola inhibits host SA biosynthesis by employing two effector proteins, EqCmu and EqPdt. These effector proteins can be delivered into plant cells to hydrolyze chorismate, the main precursor of SA, through their enzymatic activities. Notably, EqCmu and EqPdt can interact with each other, providing mutual protection against protein degradation mediated by the plant ubiquitin-proteasome system. This interaction enhances their activities in the hydrolysis of chorismate. Our study reveals a new pathogenic strategy by which two powdery mildew effector proteins cooperate to evade recognition by dampening the host immune system.IMPORTANCEPowdery mildew fungi may develop diverse strategies to disturb salicylic acid (SA) signaling in plants, which plays an important role in activating immunity, and little is known about these strategies. Our results suggest that the Erysiphe quercicola effector protein EqCmu can be translocated into host cells and inhibit host SA levels during the infection stage; however, it is targeted by the plant ubiquitin–proteasome system (UPS) and ubiquitinated, which induces EqCmu degradation. To evade the UPS, EqCmu interacts with EqPdt, another E. quercicola effector protein, to prevent that ubiquitination. EqPdt also inhibits host SA biosynthesis through its prephenate dehydratase activity. Taken together, these two powdery mildew effector proteins cause a synergistic effect in disturbing host SA signaling. Our study also suggests that enhancing SA signaling is required for boosting immunity against powdery mildew fungus.